2015
DOI: 10.1016/j.healthpol.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the EU Directive on patients’ rights and cross border health care in Malta

Abstract: The patients' rights and cross-border health care directive was implemented in Malta in 2013. Malta's transposition of the directive used the discretionary elements allowable to retain national control on cross-border care to the fullest extent. This paper seeks to analyse the underlying dynamics of this directive on the Maltese health care system through the lens of key health system stakeholders. Thirty-three interviews were conducted. Qualitative content analysis of the interviews reveals six key themes: fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…An analysis of Country Specific Recommendations (CSRs) found that the European Semester 1 system of fiscal and economic governance emphasises the financial sustainability of health systems over quality and accessibility [ 17 ]. Early analysis of the implementation of the patients’ rights and cross border care directive indicates the variable effects on Member State health systems [ 18 23 ]. These developments point to an increasingly important role for the EU in influencing health systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of Country Specific Recommendations (CSRs) found that the European Semester 1 system of fiscal and economic governance emphasises the financial sustainability of health systems over quality and accessibility [ 17 ]. Early analysis of the implementation of the patients’ rights and cross border care directive indicates the variable effects on Member State health systems [ 18 23 ]. These developments point to an increasingly important role for the EU in influencing health systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 and 2014 Malta has received Country Specific Recommendations (CSRs) calling for a comprehensive reform of the health system to improve the efficiency and sustainable use of available resources. Reproduced with permission from: [ 23 ] …”
Section: Introductionmentioning
confidence: 99%
“…2 Also, the decrease in the willingness to travel to seek care abroad could mean that unmet needs within the country were reduced following the Directive. Indeed, some literature reports that the Directive was an opportunity to implement reforms 10 including legislation on patients' rights, 16,17 the definition of health benefits package and compulsory indemnity insurance, however, although with variations across countries, 34 it seems thus that the Directive had positive spillovers.…”
Section: Discussionmentioning
confidence: 99%
“…The clarification of the entitlements made the reimbursement of health expenses in another Member-State more predictable and clarified the basket of care in the EU countries. [16][17][18] However, some restrictions in the Directive were implemented, i.e. prior authorisations for hospitalisations that require an overnight stay and highly specialised, cost-intensive healthcare.…”
mentioning
confidence: 99%
“…The breath of coverage for treatment in view of the increasing number of foreign patients on the island is also an issue of priority [24]. The requirements and obligations of the patients' rights and cross-border health care directive has put further pressure on the need to set out a publicly available list of tariffs upon which one could determine the eligibility for re-imbursement rates for cross border treatment [25,26]. It is a major challenge of the current health care system to ensure the sustainability of the system, developing the necessary mechanisms to adequately measure quality and outcomes while adapting to the new realities being faced by the most recent developments in the Maltese economy.…”
Section: Introductionmentioning
confidence: 99%